Pengaruh Pendidikan Kesehatan Tentang Pernikahan Dini terhadap Tingkat Pengetahuan dan Sikap Remaja di Puskesmas Tinggi Raja Kecamatan Tinggi Raja Kabupaten Tinggi Raja Tahun 2023 - Endang Apriyanti; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rahmah Rahmah (Lembaga Pengembangan Kinerja Dosen, 2025)
Adolescence is marked by growth and development in various aspects, including physical, psychological, and intellectual. They tend to have a great sense of curiosity, like challenges, and dare to take risks. However, this also makes them vulnerable to various risks, both in the short and long term. Therefore, health services are needed that care about the needs of adolescents, especially in terms of reproductive health. This study aims to determine whether there is an Influence of Health Education About